Representasi Identitas di Medan Pasar Seni Lukis Indonesia - Djuli Djatiprambudi (Journal of Visual Art and Design, 2007)
Since the middle of 1980s, Indonesian arts show striking growth, due to the dynamic appearance of painting market which was often referred as the boom of paintings. This phenomenon is triggered by the change of social-political-economical conditions of Asia, which are also influencing the infrastructure and suprastructure changes of the social-politics-and economy of Indonesia. It leads to the dialectical rise of the class of economical elite in Indonesia, which is dominated by the Chinese ethnic group. This group, which was politically pressurized during New Order regime, has built a tantalous room in economy. Their involvement in the arts market can bee seen as the starting point to comprehend the economical-capitalism of Indonesian Arts. It is expected that by constructing the role of Chinese ethnic group in art market, we will obtain a complete understandings of the social history of arts in Indonesia.